IFPRI-Bangladesh "Accelerators of Rural Revitalization in Bangladesh - Ahmed, Akhter (2019)
During the 2019 Global Food Policy Report Launch in Dhaka, Bangladesh, IFPRI Country Representative for Bangladesh Dr. Akhter Ahmed presents key accelerators that have driven rural growth in the country, using nationally representative data from IFPRI's Bangladesh Integrated Household Survey (BIHS) and secondary data.